Toxicity of Gompang Batu Plant Extract (Lobelia nummularia Lam) with BSLT (Brine Shrimp Lethality Test) Method as Raw Material for Medicine - Agnes Normawati Silaban; Murniaty Simorangkir (Universitas Negeri Medan, 2025)
Gompang Batu is a traditional medicinal plant found in Pangaribuan, North Tapanuli, Sumatra, Indonesia. Identification confirmed that gompang batu is Lobelia nummularia Lam from the Campanulaceae family. This study aims to determine the toxicity and phytochemical content of three types of gompang batu extracts. The Brine Shrimp Lethality Test (BSLT) method.was used for toxicity testing. Extraction was conducted through maceration using n-hexane, ethyl acetate, and ethanol solvents. LC50 values were 18.05 µg/mL for ethanol extract (very toxic), 27.59 µg/mL for ethyl acetate extract (very toxic), and 51.34 µg/mL for n-hexane extract (toxic). Phytochemical analysis showed that the ethanol extract contains abundant alkaloids, flavonoids, saponins, terpenoids and tannins. Ethyl acetate extract contains alkaloids, steroids, flavonoids, saponins, and tannins moderate tannins. N-hexane extract contains steroids and a small amount tannins. L. nummularia extract is classified as toxic and show potential as a medicinal raw material.